Role of Cannabinoid Receptors in Crocin-Induced Hypoalgesia in Neuropathic Pain in Rats - Vafaei AA; Safakhah HA; Jafari S; Tavasoli A; Rashidy-Pour A; Ghanbari A; Seyedinia SA; Tarahomi P (Dove Medical Press, 2020)
Abbas Ali Vafaei, 1, 2 Hossein Ali Safakhah, 1, 2 Simin Jafari, 1 Azin Tavasoli, 1 Ali Rashidy-Pour, 1, 2 Ali Ghanbari, 1 Seyed Ali Seyedinia, 3 Parnia Tarahomi 3 1Research Center of Physiology, Semnan University of Medical Sciences, Semnan, Iran; 2Department of Physiology, Faculty of Medicine, Semnan University of Medical Sciences, Semnan, Iran; 3Student Research Committee, Faculty of Medicine, Semnan University of Medical Sciences, Semnan, Iran*These authors contributed equally to this workCorrespondence: Ali Ghanbari Tel/Fax +98 2333654207Email ghanbari@semums.ac.irPurpose: Neuropathic pain involves injury or alteration of the normal sensory and modulatory nervous systems to produce a set of symptoms that are often difficult to treat. Previous study indicates that crocin has anti-inflammatory properties that may be mediated by the neurotransmitter system. In this study, we determine if there is an interaction between crocin and the cannabinoid system on chronic constriction injury (CCI)-induced neuropathic pain in male rats.Materials and Methods: In this experimental study, adult male Wistar rats (220– 250 g) were used. CCI was induced by setting four loose ligatures around the sciatic nerve. In part 1, after nerve lesion, vehicle, crocin (60 mg/kg) or Win 55-212-2 (0.1 mg/kg) as an agonist and AM 251 (0.1 mg/kg) as an antagonist of cannabinoid receptors were injected intraperitoneally daily in separate groups for 2 weeks. In part 2, two weeks after nerve lesion, vehicle (5 μL), crocin (6 μg/5 μL), Win 55-212-2 (0.1 μg/5 μL), AM 251 (0.1 μg/5 μL) were administered intracerebroventricularly (ICV) in separate groups. Mechanical allodynia and thermal hyperalgesia were measured using Von Frey filaments and plantar test device, respectively, at day 14. Data were analyzed by two-way ANOVA and Sidak’s multiple comparisons post-test.Results: Results indicated that centrally administered crocin significantly decreased thermal hyperalgesia and mechanical allodynia. Also, peripheral injection of crocin significantly decreased mechanical allodynia but not thermal hyperalgesia. Central or peripheral administration of Win 55-212-2 or AM  251 modulates the analgesic effect of crocin significantly.Conclusion: Our findings showed that crocin has significant analgesic effects that are probably mediated by an endocannabinoid mechanism.Keywords: neuropathic pain, crocin, rat, AM 251, Win 55-212-2